2016
DOI: 10.1136/bmjopen-2015-009259
|View full text |Cite
|
Sign up to set email alerts
|

Code Blue: methodology for a qualitative study of teamwork during simulated cardiac arrest

Abstract: IntroductionIn-hospital cardiac arrest (IHCA) is a particularly vexing entity from the perspective of preparedness, as it is neither common nor truly rare. Survival from IHCA requires the coordinated efforts of multiple providers with different skill sets who may have little prior experience working together. Survival rates have remained low despite advances in therapy, suggesting that human factors may be at play.Methods and analysisThis qualitative study uses a quasiethnographic data collection approach comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…We have realized that to aim for excellence requires us to anticipate potential failures in the system and organize to mitigate it. This is what distinguishes HROs, but such flexibility is not easily captured in available quality metrics [8,21]. Though there exists good data backing clinical targets such as time-tocompression, time-to-defibrillation and risk-standardized survival rates to dischargeareas in which our hospital has consistently performed at the top of the national American Heart Association Get-With-The-Guidelines-Resuscitation registrythere are not similar metrics for creativity, leadership, teamwork, and critical thinking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have realized that to aim for excellence requires us to anticipate potential failures in the system and organize to mitigate it. This is what distinguishes HROs, but such flexibility is not easily captured in available quality metrics [8,21]. Though there exists good data backing clinical targets such as time-tocompression, time-to-defibrillation and risk-standardized survival rates to dischargeareas in which our hospital has consistently performed at the top of the national American Heart Association Get-With-The-Guidelines-Resuscitation registrythere are not similar metrics for creativity, leadership, teamwork, and critical thinking.…”
Section: Discussionmentioning
confidence: 99%
“…An important contributor to the variability in outcomes may be the unique nature of cardiac arrest teams across hospitals. For example, respiratory therapists, social workers, pharmacists, nursing personnel and physicians all play different roles in a resuscitation in spite of common background training in Advanced Cardiac Life Support (ACLS) [8] and the recognition for interprofessional collaboration [9]. To our knowledge, no previous study has systematically asked a broad range of IHCA first-responders across multiple disciplines about their experiences with resuscitation care to directly capture their perceptions on performance.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Investigators have applied HF principles to the study of trauma resuscitation, cardiac arrest, and other areas of emergency care. 13,[20][21][22][23][24][25][26][27][28][29] In particular, HF methods have been used to examine aspects of individual performance, such as task switching exhibited by EM residents 28,30 and clinical decision-making for medical students, paramedics, and nurses. [31][32][33][34][35] Human factor methods have also been used to examine EM team performance, such as communication in trauma settings 36,37 and task saturation for those involved in rapid response and critical care transport.…”
Section: Hf In Emmentioning
confidence: 99%
“…Survival rate and better quality of care for Cardiac arrest patients varies between 2% to 49 % depending on the earlier and immediate recognition of the event, and the effective resuscitative measures taken by the resuscitative team. [8] Evidences form literatures had identified some important factors to increases the successful of in-hospital CPR and effect in the quality of patient lives. Such as, the availability of basic and advanced life support system, the immediate attempt of defibrillation and effectiveness of CPR interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Such as, the availability of basic and advanced life support system, the immediate attempt of defibrillation and effectiveness of CPR interventions. [1,2,8] It is suggested that high quality CPR increases the survival chance following CA, as long as the practitioners maintain crucial components of CPR which are minimizing the interruption of chest compression, perform adequate frequency and depth of chest compression, allow for chest expansion, and avoid access ventilation. [2] Similarly, one study had confirmed that early detection of CA, initiation of CPR and prompt management of competent and knowledgeable team are important factors to increases the survival rate.…”
Section: Introductionmentioning
confidence: 99%